2007
DOI: 10.24839/1089-4136.jn12.3.126
|View full text |Cite
|
Sign up to set email alerts
|

Underpinnings of Academic Success: Effective Study Skills Use as a Function of Academic Locus of Control and Self-Efficacy

Abstract: I t is not uncommon to hear a student blame a teacher for a low grade in a course, but the implications of such comments are not always addressed. Incidentally, these occurrences provide insight into where the student believes the control of reinforcement over an outcome exists. Within the framework of social learning theory, Rotter (1966) introduced generalized expectancies for internal versus external control of reinforcement, which refers to the belief or expectation that control of reinforcement for future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
9
1
3
Order By: Relevance
“…He found that students who possessed an internal locus of control were more likely to obtain their doctorate within 5 years than those with an external locus of control . Landis et al (2007) found that internal locus of control and high selfefficacy were related to greater academic performance. Nelson and Williams (2004) found that students' perceived academic workload and their level of external locus of control had a positive correlation with each other such that as perceived academic workload increased, so too did individual's external locus of control.…”
Section: Locus Of Control and Tertiary Studentsmentioning
confidence: 98%
“…He found that students who possessed an internal locus of control were more likely to obtain their doctorate within 5 years than those with an external locus of control . Landis et al (2007) found that internal locus of control and high selfefficacy were related to greater academic performance. Nelson and Williams (2004) found that students' perceived academic workload and their level of external locus of control had a positive correlation with each other such that as perceived academic workload increased, so too did individual's external locus of control.…”
Section: Locus Of Control and Tertiary Studentsmentioning
confidence: 98%
“…(2010) found individuals who believe they possess the ability to overcome challenges are likely to strive for achievement. Individuals who feel competent demonstrate greater willingness to apply effort while learning (Landis et al., 2007).…”
Section: Methods Of Analysis Of Self‐efficacymentioning
confidence: 99%
“…Literature suggests a correlation exists between perceived self‐efficacy and academic performance (Black, Hall, & Darmawan, 2007; Choi, 2005; Kitsantas, Winsler, & Huie, 2008). Furthermore, literature proposes pedagogical methods (Nilsen, 2009), instructor feedback (Linnenbrink & Pintrich, 2003), and internal motivation (Clayton, Blumberg, & Auld, 2010; Landis, Altman, & Cavin, 2007) impact a student's perceived level of self‐efficacy and knowledge acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Analizy odnoszące się do poczucia kontroli sięgają początków drugiej połowy XX wieku i wciąż podejmowane są w badaniach psychologicznych (por. Barani, 2006;Chubb, Fertman, Ross, 1997;Domachowski 1984;Domańska-Najder, 1984;Drwal, 1995;Gliszczyńska, 1990;Landis, Altman, Cavin, 2007;Marks, 1998;Ng-Knight, Schoon, 2017;Smith, 2003).…”
Section: Miejsce Poczucia Kontroli W Badaniach Psychologicznychunclassified